Mindfulness Training for Primary Care for Portuguese-Speaking Immigrants: A Pilot Study - Trombka, Marcelo; Creedon, Timothy B.; Demarzo, Marcelo; Cuoco, Letícia T.; Smith, Lydia; Oxnard, Alexandra C.; Rozembaque, Alana T.; Hirayama, Marcio S.; Moreno, Natalia B.; Comeau, Alexandra; Gawande, Richa; Griswold, Todd; et al. (Frontiers in Psychiatry, 2021)
Background: Portuguese-speaking immigrants are a growing underserved population in the Unites States which experience high-levels of psychological distress and increased vulnerability to mental health disorders such as depression and anxiety. Current evidence shows that Mindfulness-Based Interventions (MBI) are effective to promote physical and mental health among educated English speakers, nonetheless, the lack of diversity in the mindfulness literature is a considerable limitation. To our knowledge, the feasibility and acceptability of MBIs among Portuguese-speaking immigrant have not yet been investigated. Methods: This single-arm pilot study (N=30) explored the feasibility, acceptability, and cultural aspects of Mindfulness Training for Primary Care (MTPC)-Portuguese among Portuguese-speaking immigrants in the Boston area. MTPC is an eight-week, primary care adapted, referral-based, insurance-reimbursable, trauma-informed, MBI that is fully integrated into a healthcare system. The study also examined intervention preliminary effectiveness on mental health outcomes (depression and anxiety symptoms), self-regulation (emotional regulation, mindfulness, self-compassion, interoceptive awareness) and initiation of health behavior was explored. Results: Primary care providers referred 129 patients from 2018 to 2020. Main DSM-5 primary diagnoses were depression (76.3%) and anxiety disorders (6.7%). Participants (N=30) attended a mean of 6.1 (SD 1.92) sessions and reported a mean of 213.7 (SD=124.3) minutes of practice per week. All survey finishers would recommend the program to a friend, found the program helpful, rated the overall program as “very good” or “excellent”, and 93% would participate again, with satisfaction mean scores between 4.6-5 (Likert scale 0-5). Participants and facilitators provided feedback to refine MTPC-Portuguese culturally-responsiveness regarding materials language, settings, time, food, and community-building. Patients exhibited reductions in depression (d=0.67; p<0.001) and anxiety (d=0.48; p=0.011) symptoms, as well as enhanced emotional regulation (d=0.45; p=0.009) and among survey finishers, 50% initiated health behavior change through action plan initiation. Conclusion: This pilot study suggests that MTPC-Portuguese is feasible, acceptable, and culturally appropriate among Portuguese-speaking patients in the Boston area. Further, the intervention might potentially decrease depression and anxiety symptoms, facilitate health behavior change, and improve emotional regulation. MTPC-Portuguese investigation with larger samples in controlled studies are warranted to support its dissemination and implementation in the healthcare system.